Some determinants of employee loyalty / Mohamad Huzairi Mohamad Azam - Mohamad Azam, Mohamad Huzairi (2014)
For this research, researcher study about some determinants that would affect loyalty of employee towards the organizations. The study is to know the reasons of employee to stay in the organizations for a long period of time. This research is to review various researches in term of concepts of employee loyalty. In this regard, there are 5 dimensions of employee loyalty that been use in this research: job conditions, personal benefits, career and status, service element and locations, and commitment to managers and company. This study was both quantitative and qualitative. In this research, established questionnaire from previous research has been distributed in XYZ Sdn Bhd. The questionnaire has been distributed to 112 employees from various department in XYZ SdnBhd which are Customer Care and Township Management, Project Management, Finance, Sales and Marketing, Human Resource and System Management. Employee loyalty plays an important role in the organization in order to cope with changes, because organization need to be ready to face any change in the environment. There might be employee that might leave the organization because the level of loyalty in employee is lacking and company need to know what are the factor involve that make level of loyalty in employee decreased. Loyalty of employee in most organizations contributes significantly to the effectiveness and success of the organizations. Employees with the high level of loyalty towards company will be more productive and motivated with their job and organization. While, employees with low level of loyalty will be less motivated and more involved to absent or quit from the organization. In sense, the main purpose in conducting this study is to measure the factors that will influence level of loyalty among the employees in XYZ Sdn Bhd.